1994
DOI: 10.1007/bf01808755
|View full text |Cite
|
Sign up to set email alerts
|

Is there a difference in cognitive deficits after aneurysmal subarachnoid haemorrhage and subarachnoid haemorrhage of unknown origin?

Abstract: In a retrospective follow-up study 38 patients with aneurysmal subarachnoid haemorrhage (SAH) and 20 patients without an angiographically proven source of SAH were tested neuropsychologically one to five years after the acute event. All patients were operated on early within 72 hours if an aneurysm was proven angiographically and all were treated with nimodipine. Both patient groups had comparable cognitive deficits in spite of the less severe SAH of non-aneurysmal origin. Only in two cognitive functions the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 30 publications
0
18
1
Order By: Relevance
“…More complex tests that assess executive functions could not be used, because there is a lack of normative data for the Portuguese population and because performance on these tests is strongly influenced by education level, which was highly variable in our sample. Quality of life was not tients with aneurysmal SAH and patients with SAH of unknown origin [15,17]. Hutter et al [15] demonstrated a relationship between severity of bleeding and cognitive deficit.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…More complex tests that assess executive functions could not be used, because there is a lack of normative data for the Portuguese population and because performance on these tests is strongly influenced by education level, which was highly variable in our sample. Quality of life was not tients with aneurysmal SAH and patients with SAH of unknown origin [15,17]. Hutter et al [15] demonstrated a relationship between severity of bleeding and cognitive deficit.…”
Section: Discussionmentioning
confidence: 97%
“…Quality of life was not tients with aneurysmal SAH and patients with SAH of unknown origin [15,17]. Hutter et al [15] demonstrated a relationship between severity of bleeding and cognitive deficit. These authors reported a"diffuse" cognitive damage pattern in patients with SAH of unknown cause, in contrast with"focal" cognitive deficits in aneurysmal SAH patients.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, his may be true only in the case of moderate and relatively transient vasospasm measured by TCD. Regarding the overall effect of early aneurysm surgery, two studies reported that patients after aneurysmal SAH and early surgery and patients after SAH of unknown origin present with a comparable degree of neuropsychological impairment [26,53]. Even though surgery itself is associated with cognitive deficits, there is, however, no factual discrepancy to the above mentioned findings.…”
Section: Further Effects Of Clinical Variables and Of Early Aneurysm mentioning
confidence: 93%
“…The grade at discharge is a good predictor of impairment of cognition and memory at follow-up assessments. Patients with poor clinical grades with aneurysmal SAH are significantly more disturbed in focal cognitive functions like short-and longterm memory and word-finding capacity than patients with SAH of unknown origin that score significantly worse on neuropsychological tests [42]. Although SAH of unknown etiology represents much less of a catastrophe as compared with hemorrhage of aneurysmal origin, it does not preclude cognitive disturbances.…”
Section: Functional Consequences Of Subarachnoid Hemorrhagementioning
confidence: 98%